Transforming Church Boards into Communities - Olsen, Charles M. (Rowman & Littlefield Publishers, 1995)
Discover inspiring, practical ways your board can make its meetings become opportunities for deepening faith, developing leadership, and church renewal. Research included interviews with lay leaders; clergy; and seminary, judicatory, and denominational staff from mainline Protestant, Roman Catholic, Jewish, and Evangelical Christian faith traditions.